The Psalms I-LXXII introduction, revised version with notes and index. - Davison, W.T. (Edinburgh, Scotland T.C. and E.C. Jack)
Includes bibliographical references and index.
Annotated
Keywords: Bible. O.T. Psalms I-LXXII -- commentaries